2003
DOI: 10.1086/373883
|View full text |Cite
|
Sign up to set email alerts
|

Missense Mutations in the Regulatory Domain of PKCγ: A New Mechanism for Dominant Nonepisodic Cerebellar Ataxia

Abstract: We report a nonepisodic autosomal dominant (AD) spinocerebellar ataxia (SCA) not caused by a nucleotide repeat expansion that is, to our knowledge, the first such SCA. The AD SCAs currently comprise a group of > or =16 genetically distinct neurodegenerative conditions, all characterized by progressive incoordination of gait and limbs and by speech and eye-movement disturbances. Six of the nine SCAs for which the genes are known result from CAG expansions that encode polyglutamine tracts. Noncoding CAG, CTG, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
160
3
6

Year Published

2003
2003
2007
2007

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 229 publications
(173 citation statements)
references
References 34 publications
4
160
3
6
Order By: Relevance
“…Mutations in the PKCγ C1B domain have been implicated in the movement and cognitive disorder spinocellebellar ataxia type 14 (SCA14) [65]. Because it has been demonstrated that these mutations occur in the C1B region of PKCγ, it is assumed that this would prevent activation by oxidative signals [66].…”
Section: Pkcγ and Pkcε In Neural Tissuesmentioning
confidence: 99%
“…Mutations in the PKCγ C1B domain have been implicated in the movement and cognitive disorder spinocellebellar ataxia type 14 (SCA14) [65]. Because it has been demonstrated that these mutations occur in the C1B region of PKCγ, it is assumed that this would prevent activation by oxidative signals [66].…”
Section: Pkcγ and Pkcε In Neural Tissuesmentioning
confidence: 99%
“…On the other hand, deletion and/or point mutations were identified in the SPTBN2, KCNC3, PRKCG, and FGF14 genes, recently attributed to SCA5, SCA13, SCA14, and SCA27 respectively Waters et al 2006;Yamashita et al 2000;Chen et al 2003;Yabe et al 2003;Van Swieten et al 2003). Point mutations may result in decreased stability of the proteins, and frameshift mutations in truncated proteins (Van Swieten et al 2003;Dalski et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The expansion of noncoding trinucleotide (CAG or CTG) or pentanucleotide (ATTCT) repeats are involved in SCA8, SCA10, and SCA12 (Holmes et al 1999;Koob et al 1999;Matsuura et al 2000). Very few families are affected by missense mutations in beta-III spectrin (SPTBN2) (SCA5 (see Ikeda et al 2006)), voltage-gated potassium channel KCNC3 (SCA13 (see Waters et al 2006)), protein kinase C gamma (PKC gamma) (SCA14 (see Chen et al 2003)), and FGF14 genes (ADCA with FGF14 mutation (see van Swieten et al 2003). However, genes or even loci remain unidentified for 20-40% of families with ADCA (Sasaki et al 2003).…”
Section: Introductionmentioning
confidence: 99%